Synthesis, characterization and antioxidant activity of Schiff base and its metal complexes with Fe(II), Mn(II), Zn(II), and Ru(II) ions: Catalytic activity of ruthenium(II) complex - Turan, Nevin; Buldurun, Kenan (European Journal of Chemistry, 2018)
The synthesis, spectral, catalytic and antioxidant properties of ethyl-2-(2-hydroxy-3-methoxybenzylideneamino)-6-methyl-4,5,6-tetrahydrobenzo[b]thiophene-3-carboxylate (L) substituted iron(II), manganese(II), zinc(II), and ruthenium(II)-arene chlorides are described for the first time. The ligand and its metal complexes were characterized by elemental analysis, molar conductance, magnetic susceptibility measurements, and spectral (1H NMR, 13C NMR, FT-IR, UV-Vis and Mass) techniques. The FT-IR spectra showed that the ligand can act as bidentate or tridentate. Magnetic moments and electronic spectral studies revealed an octahedral geometry for all the complexes obtained. The thermal behavior of the complexes showed that the water molecules were separated in the first step followed immediately by decomposition of the anions and ligand molecules in the subsequent steps. Ru(II) complex was used as catalysts for the transfer hydrogenation of ketones. At the same time, the effect of various bases such as NaOH, KOH, KOBut and NaOAc as organic base were investigated in the transfer hydrogenation of ketones by 2-propanol as the hydrogen source. The complexes and ligand were tested in vitro for their antioxidant activity. The experimental results showed that Ru(II) complex had more potent antioxidant activities than Zn(II), Fe(II), Mn(II) complexes and parent ligand.